2022
DOI: 10.2196/32291
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetable Intervention to Reduce the Risk of Cancer Recurrence in Non–Muscle-Invasive Bladder Cancer Survivors: Development Using a Systematic Process

Abstract: Background Bladder cancer is one of the top 10 most common cancers in the United States. Most bladder cancers (70%-80%) are diagnosed at early stages as non–muscle-invasive bladder cancer (NMIBC), which can be removed surgically. However, 50% to 80% of NMIBC cases recur within 5 years, and 15% to 30% progress with poor survival. Current treatments are limited and expensive. A wealth of preclinical and epidemiological evidence suggests that dietary isothiocyanates in cruciferous vegetables (Crucifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In vivo and in vitro data have already demonstrated that ITCs may suppress oncogenesis and tumor progression [ 12 ]. There is also epidemiological evidence that ITCs may diminish the risk of bladder cancer recurrence [ 13 ]. However, information about AITC, BITC and PEITC is sparse, and no reports are available dealing with the influence of these compounds on drug-resistant bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro data have already demonstrated that ITCs may suppress oncogenesis and tumor progression [ 12 ]. There is also epidemiological evidence that ITCs may diminish the risk of bladder cancer recurrence [ 13 ]. However, information about AITC, BITC and PEITC is sparse, and no reports are available dealing with the influence of these compounds on drug-resistant bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17 ITCs may suppress oncogenesis and tumor progression 18 and it may diminish the risk of bladder cancer recurrence. 19 Numerous preclinical studies have shown that AITC has pharmacological activities such as antimicrobial, 20 antioxidant, 21 chemoprevention, [22][23][24] antiobesity, 25,26 anti-inflammatory, 27,28 and anticancer 29,30 activities.…”
Section: Introductionmentioning
confidence: 99%